Analysis of Numeration Ability form the Results of the Minimum Competency Assessment (AKM) in Class V Students of at SD Negeri 101 Palembang - Ridho Alhafits; Rohana Rohana; Treny Hera (Universitas Muhammadiyah Enrekang, 2023)
The numeracy abilities in the AKM results for class V students at SD Negeri 101 Palembang are classified as below the set standards. Because students do not understand the AKM numeracy questions at the level of knowing, applying and reasoning. students are not yet adept at doing numeracy questions. Fulfillment of infrastructure for working on numeracy questions, especially inadequate IT. The aim of the research is to analyze the numeracy abilities of class V students at SDN 101 PLG in terms of perceptions of Creating, Applying and Reasoning as well as analyzing the level of students' numeracy abilities. The method used is descriptive with a quantitative approach. Research with a quantitative approach, pressure analysis on numerical data (numbers) which is then analyzed using appropriate statistical methods. The sample consisted of 30 fifth grade students and data analysis used the SPSS program. The numeracy abilities of class V students at SD Negeri 101 Palembang are mostly obtained based on the results of calculations between the students' average scores and the standard deviation of the data, then the results will be determined based on norm references. At the knowledge question level, for the